2007
DOI: 10.2166/wst.2007.750
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and infiltration characteristics of pavement structures—review of an extensive monitoring program

Abstract: The stormwater runoff and infiltration performance of permeable pavements has been systematically evaluated within an intensive monitoring program. The primary objective of the investigation was to generate a broad database, which enables the development of an advanced simulation module for urban drainage modelling. Over 160 field and lab scale experiments have been completed and analyzed for surface runoff and infiltration characteristics. The test series include several pavement types under various boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 0 publications
0
21
3
1
Order By: Relevance
“…That behavior is in agreement with results reported in the literature. Illgen et al (2007), in his laboratory campaign, confirmed that the wear layer has the major influence on the infiltration capacity of the permeable pavement, while the base and sub-base layers have a minor impact and act as a storage tank. The total index is always greater than zero, which implies that all parameters influence the output variance either directly or by their interactions, and thus no parameter can be fixed without affecting the uncertainty of the output.…”
Section: Sensitivity Analysis -Scenario Imentioning
confidence: 89%
See 3 more Smart Citations
“…That behavior is in agreement with results reported in the literature. Illgen et al (2007), in his laboratory campaign, confirmed that the wear layer has the major influence on the infiltration capacity of the permeable pavement, while the base and sub-base layers have a minor impact and act as a storage tank. The total index is always greater than zero, which implies that all parameters influence the output variance either directly or by their interactions, and thus no parameter can be fixed without affecting the uncertainty of the output.…”
Section: Sensitivity Analysis -Scenario Imentioning
confidence: 89%
“…This behavior is in agreement with results reported in the literature. For example, Illgen et al (2007) reported that the water contents in the base and sub-base layers Table 7 Reduced ranges of optimized parameters for the optimization process. only marginally increased during rainfall events, and that the lower layers act as a storage tank.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Clogging, the loss of surface permeability, in PP systems has been documented by numerous researchers in both field (Bean et al, 2007;Henderson and Tighe, 2011) and laboratory based studies (Illgen et al, 2007;Pezzaniti et al, 2009;Haselbach, 2010;Tan et al, 2003). Clogging materials are deposited onto the surface of a PP from vehicular traffic, vegetative litter, atmospheric deposition and regular maintenance activities.…”
Section: Clogging Processesmentioning
confidence: 99%